Rooting response of elite cinnamon (Cinnamomum verum Bercht & Presl.) lines - KRISHNAMOORTHY, J REMA, B (Journal of Spices and Aromatic Crops, 1993)
Rooting of terminal cuttings of cinn amon (Cinnamomum verum) with indole butyric acid 2000 ppm was standardi zed. Nine elite lines of cinn amon, superior in their yield and quantity were studied for variability in their rooting capacity. Cinnamon line SL-5 was the best with high rooting percentage and good development of primary and secondary roots.